Performance evaluation of single cylinder engines using different blends of Jatropha curcas biodiesel as fuel - Asuncion, Fei Xyza B.
The researchers tested the different mixes of Jatropha oil and diesel for use as car fuel. The biodiesel with 20% Jatorpha oil was most efficient among the blends. Also, the results showed that biodiesel blends are as good as pure diesel.
Includes bibliographical references (p. 23)
Keywords: Jatropha -- Philippines; Jatropha -- Utilization -- Philippines; Jatropha -- Biotechnolog -- Philippines; Biomass energy -- Philippines